HvbZIP21, a Novel Transcription Factor From Wild Barley Confers Drought Tolerance by Modulating ROS Scavenging - Pan, Rui; Buitrago, Sebastian; Feng, Zhenbao; Abou-Elwafa, Salah Fatouh; Xu, Le; Li, Chengdao; Zhang, Wenying (Frontiers in Plant Science, 2022)
Drought stress is a common environmental stress, which adversely affects the yield and quality of crops. Due to its excellent drought tolerance, wild barley from the Middle East region is considered a valuable source for barley improvement. Here, we compared the growth rate, stomatal regulation and capacity to metabolize reactive oxygen species (ROS) of two barley cultivars and one wild barley accession. The results indicated the wild barley EC_S1 showed a faster rate of stomatal regulation and less ROS production. Transcriptomic analysis revealed that EC_S1 has slower transcriptional regulation (5050 DEGs) in the early stage of drought stress (14 d) than Baudin (7022 DEGs) and Tadmor (6090 DEGs). In addition, 30 hub genes, including nine known drought-related genes were identified by WGCNA analysis. Then, we cloned a novel bZIP transcription factor, HvbZIP21, from EC_S1. HvbZIP21 was subcellularly targeted to the nucleus. Overexpression of HvbZIP21 in Arabidopsis enhanced drought tolerance due to increasing activities of superoxide dismutase, peroxidase, and catalase activities as well as glutathione content. Silencing of HvbZIP21 in EC_S1 suppressed drought tolerance in BSMV:HvbZIP21-inoculated plants. Taken together, our findings suggest that HvbZIP21 play a critical role in drought tolerance by manipulating ROS scavenging.